The Amorites and the Bible - Burke, Aaron A. (Biblical archaeology review, 2023)
The article focuses on the Amorites mentioned in the Bible, exploring their identity and portrayal by biblical writers. It discusses their association with Canaan, their descent from the Nephilim, their inhabitation of various regions, and their connection to deviant religious practices. Additionally, it highlights the presence of Amorite fortifications and their influence on the biblical landscape.